Investigation of the consistency between reported chief complaint and periodontal health status of Iraqi patients in relation to age and gender (A retrospective study) - Ali A Abdulkareem; Hayder R Abdulbaqi; Ahmed K Nayyef; Saif S Saleem (College of Dentistry/ University of Baghdad, 2019)
Background: Chief complaint of patients attending dental clinic represents the first step towards treatment plan. However, most of patients are not aware but the extent and severity of periodontal disease, which could be also, misdiagnose by the dentist. Aim of the study: To investigate whether reported chief complaint(s) are consistent with oral hygiene status Materials and methods: Records of 1102 patients, attending periodontics clinics in the college of dentistry/ university of Baghdad, were used to determine ten most commonly reported chief complaints. Sample of patients was further subdivided according to gender and age. In addition, plaque and gingival index were recorded to determine oral hygiene status. Results: Patients mostly attend clinic of periodontics in response to motivation by dental students or staff members or referred from other department. Further, removal of stain or deposits from their teeth represented the highest chief complaint (32%). Other true periodontal signs were seldom reported in spite of significantly high plaque and gingival index (P<0.05) with increasing age. Conclusion: Nation-wide educational programs are needed due to discrepancy between reported chief and periodontal health status. In addition, the actual need of patients, which was mainly oriented towards scaling, reflects ignorance and lack of knowledge about nature and alarming signs of disease.